Evaluation of amplicon-based nanopore sequencing for foot-and-mouth disease viruses in clinical and environmental samples - Ji Hyun Jeon; Soyoon Ryoo; Hyeonjeong Kang; Jongwan Kim; Da-Rae Lim; Antonello Di Nardo; Andrew E. Shaw; Donald P. King; Su-Mi Kim (Microbiology Spectrum, 2026)
ABSTRACT Foot-and-mouth disease (FMD) causes severe global economic loss, necessitating rapid viral characterization. Nanopore sequencing provides a simple, real-time workflow suitable for on-site outbreak response, addressing the limitations of conventional methods. In this study, we optimized a previously published amplicon-based protocol and used this method to characterize a diverse range of samples (vesicular fluid, epithelium, serum, nasal/oral swabs, and environmental samples) collected during FMD outbreaks in 2025 in the Republic of Korea. Of the 129 samples collected, we successfully recovered complete genomes from 37 samples and VP1 sequences from 85 samples. Amplifying the S-fragment in isolation and separately barcoding each pool of PCR amplicons markedly improved sequence recovery. Furthermore, sequencing success depended on viral load and sample type. Based on comparisons with real-time RT-PCR results, whole-genome sequence (WGS) recovery exceeded 77.3% at cycle threshold (Ct) values ≤25 across all clinical samples. In the Ct > 30 category, serum samples yielded the highest WGS recovery rates (44.4%). This rate was markedly higher than the success rates observed for epithelium (20.0%) and nasal swabs (9.1%), whereas oral swabs and environmental samples failed to yield any sequences (0%). However, VP1 recovery from environmental samples reached 80% at Ct ≤ 30 (8/10), providing an approach to enable non-invasive monitoring. These findings demonstrate that amplicon-based nanopore sequencing is a practical method for the rapid generation of genomic data during FMD outbreaks. IMPORTANCE Although rapid detection and genomic data analysis are crucial for effective foot-and-mouth disease (FMD) control, the collection of these data can be challenging for certain sample types and impacted by reduced viral loads that result from nationwide FMD vaccination. This study provides a practical solution through large-scale evaluation of an optimized amplicon-based nanopore sequencing protocol to enhance the sequencing success rates for both clinical and environmental samples. Using a modified protocol to enhance genome recovery, we demonstrated that sequence data could be retrieved from diverse sample types (even with high real-time RT-PCR cycle threshold values). We identified serum as the most suitable sample, with environmental sample sequencing allowing for non-invasive monitoring during outbreaks. These results support the use of nanopore sequencing for rapid genomic analysis, particularly in outbreak responses, such as rapid surveillance, emergency vaccine selection, and epidemiological monitoring.